RETRACTED: Financial Inclusion, Technological Innovations, and Environmental Quality: Analyzing the Role of Green Openness - Ahmad, Mahmood; Ahmed, Zahoor; Bai, Yang; Qiao, Guitao; Popp, József; Oláh, Judit (Frontiers in Environmental Science, 2022)
Undoubtedly, financial inclusion (FIN) contributes to economic development by enabling individuals and businesses, particularly small and medium enterprises, to access financial services. Financial inclusion may also have environmental implications; however, limited studies have looked into the nexus between financial inclusion and environmental quality. Also, the possible impacts of technological innovation and green openness remain unexplored in this nexus. In this context, this article probes the relationship between financial inclusion, technological innovation, green openness, and CO2 emissions in BRICS countries while controlling for economic development and energy consumption. Using the panel times series data from 2004 to 2018, this study uses advanced econometric techniques for empirical analysis robust to cross-sectional dependency and slope heterogeneity. The empirical results unveiled that FIN contributes to environmental degradation in BRICS countries. In contrast, technological innovation and green openness pose mitigating effects on emissions, thus promoting environmental sustainability. Environmental degradation is evidenced to enhance due to rising economic growth and energy utilization. Financial inclusion, technical innovation, and green openness Granger cause CO2 emissions, but not the other way around. Further, technological innovation, green openness, and financial inclusion Granger cause each other. Based on the empirical results, this study recommends that BRICS countries should promote technological innovation, green openness, and at the same time, integrate financial inclusion with environmental policies to achieve climate-related goals.